Efektivitas Terapi Musik Klasik Mozart terhadap Penurunan Stres dalam Menyusun Karya Tulis Ilmiah (KTI) pada Mahasiswa Tingkat Akhir Prodi DIII Keperawatan Universitas Abulyatama - Alfiaturrahmi Alfiaturrahmi; Fauziah Fauziah; Nurul Sakdah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
The situations frequently faced by final-year students while preparing scientific papers often have an impact on their mental health and learning process. The purpose of this study was to evaluate the effectiveness of Mozart music therapy in reducing stress among final-year students in the Diploma III Nursing Program at Abulyatama University. This study used a quantitative method with a one-group pre-Test and post-Test design. The population studied included all final-year students in the Diploma III Nursing Program at Abulyatama University, totaling 168 students. The sample consisted of 15 respondents selected using purposive sampling technique. The instrument used in this study was the DASS-42 questionnaire with a Cronbach’s Alpha value of 0.8806, and Mozart classical music therapy was administered in accordance with the Standard Operating Procedure sheet. This research was conducted from May 20 to May 23, 2025. Data analysis used the T-test. The results showed a decrease in the mean stress score from 26.07 (pre-Test) to 20.67 (post-Test), with a p-value = 0.000. Based on these results, it can be concluded that Mozart classical music therapy has an effect in reducing stress among final-year students during the process of writing scientific papers. It is expected that students can make Mozart classical music therapy a routine practice in daily life to maintain mental balance, and educational institutions are advised to organize Mozart classical music therapy programs regularly as a preventive effort against academic stress